Guinness world records 2017 - Glenday, Craig; Guinness World Records Limited ([London, England] Guinness World Records, 2016)
Chronicles the evolution of record breaking while incorporating thousands of new entries, hundreds of new photographs, and highlights of classic records.
Includes index.
"Over 4,000 records & photos! Plus, exploring space with Buzz Aldrin & Chris Hadfield!"--Page [1] of cover.
Cover title.
Keywords: Curiosities and wonders; World records; Curiosities and wonders; World records